Vegetation estimation using Normalized Difference Vegetation Index (NDVI) from satellite NOAA/AVHRR data over Mongolia - D, Azzaya; V.K, Dadhwal (Scientific transaction of the National University of Mongolia. Physics, 2022)
The purpose of this research work was to estimate the vegetation cover and to compare the satellite images and stations data.